Serum Biomarkers IL-6 and HIF-1α in Rosacea: Assessing Their Significance in Disease Pathogenesis and Telangiectasia Formation - Gamze Tas Aygar; Bengü Çevirgen Cemil; Fevzi Nuri Aydın; Volkan Buran; Selda Pelin Kartal (Mattioli1885, 2024)
Introduction: Rosacea, a chronic inflammatory disease primarily affecting the central part of the face, is a complex condition whose mechanisms are still not fully understood. However, research has indicated a positive correlation between two molecules: Hypoxia-inducible factor-1α (HIF-1α) and Interleukin-6 (IL-6). The levels of HIF-1α in rosacea patients have yet to be assessed. Objectives: In this study, the aim was to assess the levels of HIF-1α and IL-6 in patients with rosacea in relation to both the severity of the disease and the primary and secondary clinical manifestations of the condition. Methods: The study included patients diagnosed with rosacea and sex-and age-matched healthy volunteers (N: 40, N: 40). Serum HIF-1α and IL-6 levels were quantified using enzyme-linked immunosorbent assay (ELISA). Results: When compared to the control group, serum levels of HIF-1α and IL-6 were significantly elevated in the patient group. A positive correlation was found between the level of HIF-1α and the severity of the disease (r: 0.374, p: 0.017). Furthermore, a significant association was observed between the presence of telangiectasia, one of the primary symptoms, and HIF-1α (r: 2.401, p: 0.016). Conclusion: The significantly elevated levels of IL-6 and HIF-1α in patients with rosacea compared to the control group support the hypothesis that they play roles in the pathogenesis of the disease. The correlation of HIF-1α with the severity of the disease and its significant elevation in patients with telangiectasia suggest its potential involvement in the pathogenesis of the disease, particularly in the formation of telangiectasia.